The stolen crystals - Harrison, Paula (New York : Scholastic, Inc., 2013)
Princess Jaminta lives in the beautiful Kingdom of Onica. She and her fellow princesses have discovered that someone is out to steal one of the kingdom's greatest treasures, and might harm a baby panda in the process. The Rescue Princesses must leap into action!
680
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Animal rescue -- Juvenile fiction; Pandas -- Juvenile fiction; Children's stories